Preoperative Vs Postoperative Radiosurgery For Resected Brain Metastases: A Review. Issue 1 (16th May 2018) - Prabhu, Roshan S; Patel, Kirtesh R; Press, Robert H; Soltys, Scott G; Brown, Paul D; Mehta, Minesh P; Asher, Anthony L; Burri, Stuart H
Abstract: Patients who undergo surgical resection of brain metastases are at significant risk of cavity local recurrence without additional radiation therapy. Postoperative stereotactic radiosurgery (SRS) is a method of focal treatment to the cavity to maximize local control while minimizing the risk of neurocognitive detriment associated with whole brain radiation therapy. Recently published randomized trials have demonstrated the benefit of postoperative SRS in terms of cavity tumor control and preserving neurocognition. However, there are several potential drawbacks with postoperative SRS including a possible increase in symptomatic radiation necrosis because of the need for cavity margin expansion due to target delineation uncertainty, the variable postoperative clinical course and potential delay in administering postoperative SRS, and the theoretical risk of tumor spillage into cerebrospinal fluid at the time of surgery. Preoperative SRS is an alternative paradigm wherein SRS is delivered prior to surgical resection, which may effectively address some of these potential drawbacks. The goal of this review is to examine the rationale, technique, outcomes, evidence, and future directions for the use of SRS as an adjunct to surgical resection. This can be delivered as either preoperative or postoperative SRS with potential advantages and disadvantages to both approaches that will be discussed.